The burden of non-communicable disease risk factors in a low-income population: Findings from a cross-sectional study highlighting the prevalence of obesity, hypertension, and metabolic disorders in the south of Quito, Ecuador - Sergio Morales-Garzón; Juan Vasconez; Jessica Pinto Delgado; Francisco Barrera-Guarderas; Elisa Chilet-Rosell; Marta Puig-García; Andrés Peralta; María Fernanda Rivadeneira Guerrero; Ana Lucía Torres-Castillo; Lucy Anne Parker (PLoS ONE, 2025)
Objectives We describe the prevalence of Non-Communicable Disease (NCD) risk factors in a low-income health district in the South of Quito, Ecuador. Study design We conducted a cross-sectional study between November 2020 and October 2021 Methods We used multi-stage cluster sampling to select 656 of población total adult residents of 17D06 health district, enabling a prevalence estimation with at least ±5.73% absolute precision. We collected socio-demographic information and behavioural risk factors using the expanded WHO STEPwise approach to NCD surveillance. We measured height, weight, and blood pressure, and collected blood samples to assess glucose levels, lipid profiles, and renal function. We estimated the prevalence of behavioural and metabolic NCD risk factors by sex and age groups (18–44, 45–69, and >70). Results One-third of participants were obese (33.2% overall, 148 women, 38,7%, and 41 men, 22%), and more than half had a raised waist circumference (56.8%, N = 322). Hypertension affected 26.9% of participants (63 men, 33% and 90 women, 24%). Hyperglycaemia affected 7.9% (N = 45) of participants and increased with age and peaked at 22% among women over 70. More than half of the participants presented hypercholesterolemia (317 individuals, 56.2%). Low consumption of fruit and vegetables, high salt consumption and high sugar consumption were common in all population groups (88.4%, N = 580, 33.2%. N = 218 and 72.4%, N = 475, respectively). Conclusions The critical prevalence of NCD risk factors in this low-income urban district of Quito, alongside similar trends observed in other settings across Latin America, underscores the need for ecological public health strategies to create healthy environments and promote healthier behaviours. Gender-sensitive approaches may be useful to address differences between sexes.